Functional testing in a mouse stroke model induced by occlusion of the distal middle cerebral artery - Lubjuhn, Judith; Gastens, Alexandra; von Wilpert, Gertrud; Bargiotas, Panagiotis; Herrmann, Oliver; Murikinati, Sasidhar; Rabie, Tamer; Marti, Hugo; Amende, Ivo; Hampton, Tom G.; Schwaninger, Markus (Journal of neuroscience methods, 2009)
Reducing post-stroke disability is the major goal of stroke therapy. Consequently, functional testing is essential in experimental stroke studies to increase the predictive value of animal models. We used several sensory and motor tests to assess functional disability in a mouse model of permanent distal middle cerebral artery occlusion (pdMCAO) that induced mainly cortical infarcts. Gait dynamics were transiently disturbed after pdMCAO as measured by different analysis techniques. Stance and brake duration were shorter after pdMCAO. Consistent with sensory and motor deficits the latency to move was prolonged up to 14 days after pdMCAO and the performance in the corner test and handedness were affected on day 1 or 2 after pdMCAO. Heart rate was decreased and heart rate variability were increased after pdMCAO indicating sympathetic-parasympathetic imbalance. In summary, pdMCAO-induced cortical infarcts lead to clinically relevant sensory, motor and cardiac autonomic dysfunction in mice. The present study provides a basis to explore the potential of functional testing for neuroprotection and neuroregeneration after stroke.
Gesehen am 19.04.2023